Potential Advantages of Bioactive Compounds Extracted From Traditional Chinese Medicine to Inhibit Bone Destructions in Rheumatoid Arthritis - Shi, Yingjie; Shu, Haiyang; Wang, Xinyu; Zhao, Hanxiao; Lu, Cheng; Lu, Aiping; He, Xiaojuan (Frontiers in Pharmacology, 2020)
Bone destruction is an important pathological feature of rheumatoid arthritis (RA), which finally leads to the serious decline of life quality in RA patients. Bone metabolism imbalance is the principal factor of bone destruction in RA, which is manifested by excessive osteoclast-mediated bone resorption and inadequate osteoblast-mediated bone formation. Although current drugs alleviate the process of bone destruction to a certain extent, there are still many deficiencies. Recent studies have shown that traditional Chinese medicine (TCM) could effectively suppress bone destruction of RA. Some bioactive compounds from TCM have shown good effect on inhibiting osteoclast differentiation and promoting osteoblast proliferation. This article reviews the research progress of bioactive compounds exacted from TCM in inhibiting bone destruction of RA, so as to provide references for further clinical and scientific research.